ANALISIS PROSEDUR PELAKSANAAN PENGELOLAAN DANA DESA PADA DESA PASSI 2 KECAMATAN PASSI BARAT - Bawon, Rizky Wahyudi; Karamoy, Herman; Warongan, Jessy D.L (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Village Fund Management requires accountability of an apparatus in its management and it is necessary to apply good governance principles that is accountability. In village fund management, the village government planning phase prepares the village government's annual financial plan as set forth in the Village Revenue and Expenditure Budget (APBDesa). It is also very important to be understood precisely and correctly is the duties and responsibilities of each village fund manager. The purpose of this study is to find out how the procedure of the implementation of village fund management in Passi 2 Village of West Passi District. The method used is descriptive method. The results showed that the management and accountability of Village Funds in Passi 2 Village West Passi District Bolaang Mongondow Province North Sulawesi Province has been in accordance and have followed the procedures based on Law no. 113 Year 2014 on the management of Village Funds where the intended target is the Village and in implementing its program discussed with the Village Government and Village People's Consultative Board (BPD).Keywords: Management, Accountability, Village Fund